Pengembangan Pengembangan Media Monopoli Pada Tema Makananku Untuk Menumbuhkan Pemahaman Konsep Siswa Kelas VIII di SMP Cilegon - Putri Amelia; Dwi Indah Suryani; Septi Kurniasih (UNIB Press, 2023)
Learning activities in schools still lack teachers in using learning media, students still like to play during learning, and teachers still use conventional methods in explaining material, which can lead to a lack of understanding of concepts in students. Based on these problems, researchers developed creative and interesting media, as well as game-based media in the form of monopoly media. Monopoly media is a game-based educational media to help students grow their understanding of concepts which are structured based on indicators of concept understanding. The aim of this research is to determine the design and describe the level of efficiency of monopoly media on the theme of my food being developed. The research method used is Research and Development (R&D) according to Thiagarajan (1974) which is limited to three stages, namely (1) Define, (2) Design, and (3) Develop. The results of the research are the design of the monopoly board media in the form of questions and information contained on the board and cards containing questions and information about my food which are arranged according to indicators of concept understanding. The monopoly media validation results from the validator were obtained at 92.11% in the